Evolution of the brown spot (Septoria glycines) in different soybean (Glycine max) production systems - Lavilla, M.; Peper, A. (Agronomía Mesoamericana, 2024)
Introduction. The main control measure for brown spot (BS) caused by Septoria glycines is through the application of foliar fungicide. However, the management of the disease could be accomplished through cultural and genetic practices. Objective. To analyze the evolution of BS in soybean under different production systems. Materials and methods. This study was conducted for two consecutive years (2020 and 2022), in Pergamino, Buenos Aires, using the soybean cultivar DM46i20. The management variables studied were cover crops (CC), rotations (Rt), and timing of foliar fungicide application (MAFF). The evaluated pathometric variable was the area under the progress curve of plant height with symptoms (ABCPAPS), and the quantitative physiology variable was grain yield (R) in kg/ha. Results. Agronomic management practices had a significant effect (p≤0.05) on R and ABCPAPS. CC and MAFF were independent variables and showed a significant response (p<0.0001) on R. On the other hand, there was a significant triple interaction (p<0.0001) among CC, Rt, and MAFF for ABCPAPS, and therefore, the data were explained based on this relationship. Conclusions. The implementation of cover crops, crop rotations, and foliar fungicide significantly reduced (p≤0.05) the evolution of BS in soybean cultivation. There was a significant negative correlation (p≤0.05) between soybean yield and the area under the progress curve of the plant height with BS symptoms.